Knowledge and practice on Toxoplasma infection in pregnant women from Malaysia, Philippines, and Thailand - Andiappan, Hemah; Nissapatorn, Veeranoot; Sawangjaroen, Nongyao; Khaing, Si-Lay; Salibay, Cristina C.; Cheung, Mary Mae M.; Dungca, Julieta Z.; Chemoh, Waenurama; Xiao Teng, Ching; Lau, Yee-Ling; Mat Adenan, Noor A. (Frontiers in Microbiology, 2014)
Toxoplasma gondii, is one of the infectious agents of congenital TORCH infections, causes severe clinical outcomes in fetus and newborns. Nevertheless this life-threatening parasitic disease is preventable by simple preventive measures related to lifestyle during pregnancy. We aim to study on the knowledge about toxoplasmosis and practices that prevents this infection among the pregnant women. Total of 2,598 pregnant women from Malaysia, Philippines and Thailand were randomly surveyed to determine the knowledge and their practices on Toxoplasma infection. The questionnaire covered respondents’ general information and knowledge on plausible risks factors, symptoms, timing of infection, prevention knowledge and preventive behavior regarding Toxoplasma infection. Majority of these pregnant women were in their age group of 20-29 years (50.9%), completed secondary level of education (51.7%), in their second trimester of pregnancies (38.1%), non parous (36.6%) and had no history of abortion (90.4). Based on this survey, only 11% of these pregnant women had read, heard or seen information regarding toxoplasmosis and 3.5% of them were aware of being tested for the infection. A small percentage of these pregnant women knew that T. gondii were shed in the feces of infected cats (19.4%) and sometimes found in the raw or undercooked meat (11.0%). There was 16.1% of responding women knew that toxoplasmosis is caused by an infection. Demographic profiles such as age group, level of education, pregnancy term and number of children of the pregnant women showed significant association with their responses towards prevention knowledge and preventive behavior related questions (P<0.05). Thus, it is suggested that health education on toxoplasmosis and primary behavioral practices should be consistently offered to reproductive age women in general and pregnant women in particular. This information could help to reduce vertical transmission of Toxoplasma infection during pregnancy.